Viet’s Theorem, Viet’s Generalized Theorem - Xudoyberdiyevich, Ruziyev Jamshid (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article, Viet’s theorem is explained in detail and the operations related to this theorem are introduced.